Lemma micromorphology in Cathestecum (Poaceae: Chloridoideae: Boutelouinae) - Pacheco Rivera, Darisol; Dávila Aranda, Patricia (Instituto de Ecología, A.C., 2003)
Given the taxonomical utility of lemma epidermis characters and the scarcity of such information for the genus Cathestecum, these characteristics are examined, described and compared with those of related genera in the subtribe Boutelouinae in order to elucidate possible characters of taxonomic value. The most significant results were the presence of papillae in C. tamaulipense, C. erectum and C. brevifolium var. sonorense, the absence of prickles and cork cells in C. brevifolium and the absence of silica bodies in all species of Cathestecum. Related genera (Buchloë, Soderstromia, Griffithsochloa, Pentarrhaphis and Bouteloua), each one represented by a single species (except Bouteloua and Pentarrhaphis), have abundant papillae (not observed in Bouteloua eludens and Griffithsochloa multifida) and cork cells. Silica bodies were observed only in Buchloë dactyloides. It is concluded that some of the micromorphological characters studied may be of taxonomic value for separating species of Cathestecum, as well as for establishing, along with others morphological sources, relationships among the taxa of subtribe Boutelouinae.